Produção biotecnológica de xilitol a partir de hidrolisado de bagaço de caju - Albuquerque, Tiago Lima de (2014)
The use of agro-industrial waste as raw material for the production of products with higher added value has received great attention in the scientific field in recent years. These materials are discarded into the environment, leading to large - scale environmental damage or, when used, are not employed fully and sustainably. Brazil stands out in global agricultural production of various products, being the northeast region's the largest domestic producer of cashew apple, so including the country in a situation of global spotlight in rel ation to this crop. Processing, retires almond cashew apple, which is usually exported with excellent market price, and extract the juice, leaving a considerable amount of bagasse. This component, in turn, has commercial price , being used as fertilizer and as animal feed supplement. Cashew apple bagasse (CAB) is rich in cellulose ( 1 7.73 %) and hemicellulose (19.22%), which makes it a suitable lignocellulosic material to obtain ing various fermentable sugars, especially glucose and xylose. These carbohydrates can be assimilated by microorganisms producing, through microbial fermentation, several byproducts such as xylitol. This substance is a polyol with food, pharmaceutical and dental importance. Industrial production occurs by hydrogenation catalyzed by the presence of metal alloys, D - xylose, under conditions of high temperatures and pressures, which increases the cost of process. Several microorganisms, especially yeast, are reported by their ability to produce xylitol from lignocellulosic waste s . Thus, the aim of this work was to evaluated the employability of CAB as substrate for xylitol production by microbial fermentation. In t he first stage of the research , xylitol production in synthetic media composed of xylose (MX) or xylose and glucose (MXG), by thre e yeasts was evaluated : Candida tropicalis , Kluyveromyces marxianus CCA510 and Kluyveromyces marxianus ATCC36907. The three yeasts were able to produce xylitol in synthetic media and C. tropicalis and K. marxianus CCA510 have been selected for their best p erformance for the following experiments. The second stage of the work was to evaluate the production of xylitol from hemicellulosic cashew apple bagasse hydrolysate (CABH). The hydrolysate was obtained by subjecting the CAB, after prior washing, drying an d standardization of size, to acid hydrolysis with H 2 SO 4 0.6 mol L - 1 , leading to concentrations of glucose and xylose of 12.09 g.L - 1 and 19.02 g L - 1 , respectively. The CABH was concentrated by evaporation and treated with two types of activated carbon (gra nular or powder), noting that charcoal powder was more effective in eliminating microbial fermentation inhibitors (such as acetic acid, formic acid and phenolic compounds). Finally, it was evaluated the influence of supplementation of CABH with different n itrogen sources (urea, ammonium sulfate and yeast extract) for the production of xylitol. It was concluded that urea was able to improve growth in biomass of the microorganisms tested, however, none of the sources of nitrogen were significant for increasin g the production of xylitol. It was concluded that the CABH is a potential feedstock for the biotechnological production of xylitol by yeast and detoxification treatment and nutritional supplementation may be considered to improve the process.